A Technique To Address Four-Layed DANP Method - Zeeshan, Asim; Sorooshian, Shahryar; Muzamir, Hasan (IAEME Publication, 2018)
This study attempt to diagnose DANP (DEMATEL based ANP) method with their characteristics that applied on three layer Multi-criteria decision making, MCDM, (goal, dimension, criteria) still unable to utilized on fourth layer MCDM scenario (dimension, criteria, sub- criteria, or sub-sub criteria). From previous research studies on DANP (DEMATEL based ANP) where the normalized total influential matrix ( ) belongs to dimension use to multiple with un-weighted super matrix that belong to criteria that obtained weighted supermatrix W* the major limitation of such technique is the interdependency among dimensions and criteria restricted to three layered Multicriteria decision making. This study explores a novel technique to utilize DANP (DEMATEL based ANP) as applicable for four layers Multicriteria decision-making tool. The proposed technique addresses the potential inadequacy from prior studies and offers more agile approach that allows decision makers to respond according to complex situation. Key words: DEMATEL; ANP; DEMATEL